2007
DOI: 10.1074/jbc.m705219200
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Growth Hormone Action in Osteoblasts

Abstract: Growth hormone (GH) affects bone size and mass in part through stimulating insulin-like growth factor type 1 (IGF-1) production in liver and bone. Whether GH acts independent of IGF-1 in bone remains unclear. To define the mode of GH action in bone, we have used a Cre/loxP system in which the type 1 IGF-1 receptor (Igf1r) has been disrupted specifically in osteoblasts in vitro and in vivo. Calvarial osteoblasts from mice homozygous for the floxed IGF-1R allele (IGF-1R flox/flox ) were infected with adenoviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 52 publications
4
71
0
2
Order By: Relevance
“…Indeed, GH can exert both IGF-Idependent and IGF-I-independent actions to regulate bone cell and chondrocyte functions. For example, GH could stimulate ERK and Akt phosphorylation and inhibit apoptosis in cultures of osteoblasts lacking IGF-IR expression, but fail to induce cell proliferation in the same cultures (70). Moreover, we (50) showed that GH could stimulate bone formation even in the global IGF-I KO mice, although not to the extent of IGF-I replacement.…”
Section: Integration Of Local Igf-i/igf-ir Signaling With Systemic Homentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, GH can exert both IGF-Idependent and IGF-I-independent actions to regulate bone cell and chondrocyte functions. For example, GH could stimulate ERK and Akt phosphorylation and inhibit apoptosis in cultures of osteoblasts lacking IGF-IR expression, but fail to induce cell proliferation in the same cultures (70). Moreover, we (50) showed that GH could stimulate bone formation even in the global IGF-I KO mice, although not to the extent of IGF-I replacement.…”
Section: Integration Of Local Igf-i/igf-ir Signaling With Systemic Homentioning
confidence: 82%
“…Studies by Gan and colleagues showed that GH can promote the formation of GHR/JAK2/IGF-IR complex to facilitate GHR signaling in osteoblasts (71), indicating a novel complementation between GHR and IGF-IR signaling, which could be a basis for some IGF-IR-dependent GH actions. The fact that OCN IGF-IR KO mice failed to respond to GH treatment to increase bone mass suggests that IGF-IR-dependent actions of GH are the predominant responses to promote skeletal anabolism (70). It, however, remains unclear regarding the sources of IGF-I that respond to GH and promote osteoblast functions in the bone.…”
Section: Integration Of Local Igf-i/igf-ir Signaling With Systemic Homentioning
confidence: 94%
“…A role of IGF/IGFBP signaling in age-related bone loss is supported by the finding that high levels of IGFBP2 correlate with increased bone turnover in aged men and women (100). Although GH promotes osteoblastic cell proliferation and differentiation (101), its effects on osteoblasts are mainly mediated by IGF1 (102). Genetic models in mice indicate that endogenous IGF1 increases bone formation and bone mass, which is more significant at the cortical than at the trabecular bone level (103,104).…”
Section: Growth Factorsmentioning
confidence: 99%
“…Growth hormone (GH)/IGF-1 signaling is known to play a major role in osteoblastogenesis and bone formation [53,57,58]. The actions of GH in osteoblasts are in part mediated by STAT5 activation which upregulates IGF-1 expression [51,59]. IGF-1 signaling in turn activates RUNX2 activity and promotes osteoblast differentiation in MSC [60][61][62].…”
Section: Discussionmentioning
confidence: 99%